Mumarasah al-Ta'lim al-Musagar li Tarqiyah Maharah al-Kalam fi Syu'bah Ta'lim al-Lugah al-Arabiyah - Ana Konita; Ahmad Kamil Fadoli (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2021)
As it is known that micro-teaching at the Islamic University of Jember is carried out through "youtube" during the Covid-19 pandemic, but the learning process cannot be separated from challenges and problems. A qualitative descriptive approach was used in this study. Collecting data by observation, interviews, and documentation. and data analysis used by Mills and Huberman three methods, namely data reduction, presentation, and inference. This study aims to describe the application of micro-teaching practices to improve speaking skills in Arabic education study programs during the pandemic. The results showed that the practice of micro-teaching at the Islamic University of Jember was carried out through "youtube" during the Covid 19 pandemic. The challenge is that qualified teacher candidates must be able to adapt to all circumstances so that education continues, while one of the obstacles is that some students find it difficult to the learning process because the process is through technology.